ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI TEH (Studi Kasus: PTPN IV Bahbutong, Kec. Sidamanik, Kab. Simalungun Sumatera Utara) - Desi Apriani Damanik; Azwar Harahap; Eka Armas Pailis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to analyze the capital, labor and raw materials impact of positive and negative and to understandthe most dominant factor of production that influence the tea production in PTPN IV Bahbutong. Thedata used are secondary data from PTPN IV Bahbutong. The analysis used in this study is a double linear regression analysis with the functions of the Cobb-Douglas production, using a software tools SPSS version 21, and the data used isa quarterly data during the period of 2009 to 2014. The results of the Cobb-Douglas analysis shows that estimation model a production function namely LnY = -10,105 + 0,199LnX1 + 0,956LnX2 + 0,646LnX3. The coefficient of determination (R2) of the dependent variable is able to explain the dependentvariables is of capital, raw materials, and labor (94,4%) of the remaining 5,6% is explained by other factors outside the model. Meanwhile, results of the regression analysis indicates that in its own production factors that influence results positively and significantly to the production of tea is the capital, materials and labor. Testing as a whole is using the F where F-sums (130,898) > F-table ( 3,10), which means variable capital , raw materials, and labor together can beinfluential to the results of tea production.Keywords: Production factor, Cobb Douglas, and Linear Regression